ANALYSIS OF IMPLEMENTATION CONTINUUM OF CARE PROGRAM TO INFANTS AND CHILD UNDER 5 YEARS HEALTH SERVICE - novi zetri utami (HUMAN CARE JOURNAL, 2018)
Deaths of children under 5 years are caused by pneumonia, diarrhea, malaria, disease complications, premature, asphyxia, sepsis, accident, congenital abnormalities, and nutritional disorders. To reduce the number of such deaths, the WHO and other world organizations advocating for Continuum Of Care. The research by methods qualitative research, with a phenomenological approach. The study was conducted in the working area of the health department of Bukittinggi city, in September-October 2017. Informants election by purposive sampling. Data collection was conducted through interviews and processed and analyzed qualitatively. The results are known inputs such as policy refers to the vision and mission of the mayor, the amount of power is not sufficient, the availability of sufficient funds, the availability of sufficient infrastructure. Proces is implementation of the program should be increased. And output obtained, the Continuum Of Care program in the primary health center Bukittinggi 2016 has not been achieved, because the target is too high and the lack of participation of the community to visit health facilities as well as enhanced cooperation with the relevant sectors. It was concluded that Continuum Of Care program the primary health center has not reached Minimum Service Standard Bukittinggi City and is expected to improve the service even better.